An analytical model for the design of corner combined footings - Arnulfo; López Chavarría, Sandra; Medina Elizondo, Manuel; Sandoval Rivas, Ricardo; Farias Montemayor, Oscar Mario (Revista ALCONPAT, 2020)
This work shows an analytical model for the design of corner combined footings subjected to an axial load and two orthogonal flexural moments per each column. It considers the real pressure on the ground below of the footing, and the methodology is based on the principle that the integration of the shear force is the moment. The current design considers the maximum pressure at all contact points. This model is verified by equilibrium of shear forces and moments. The application of the model is presented by means of a numerical example. Therefore, the proposed model is the most appropriated, because it generates better quality control in the resources used.